Comparison of propofol and dexmedetomidine infused overnight to treat hyperactive and mixed ICU delirium: a protocol for the Basel ProDex clinical trial. Issue 7 (13th July 2017) - Hollinger, Alexa; Ledergerber, Katrin; von Felten, Stefanie; Sutter, Raoul; Rüegg, Stephan; Gantner, Lukas; Zimmermann, Sibylle; Blum, Andrea; Steiner, Luzius A; Marsch, Stephan; Siegemund, Martin
Abstract : Background/objectives: Delirium is a neurobehavioural disturbance that frequently develops particularly in the intensive care unit (ICU) population. It was first described more than half a century ago, where it was already discovered as a state that might come along with serious complications such as prolonged ICU and hospital stay, reduced quality of life and increased mortality. However, in most cases, there is still lack of proof for causal relationship. Its presence frequently remains unrecognised due to suggested predominance of the hypoactive form. Furthermore, in the general ICU population, it has been shown that the duration of delirium is associated with worse long-term cognitive function. Due to the multifactorial origin of delirium, we have several but no incontestable treatment options. Nonetheless, delirium bears a high burden for patient, family members and the medical care team. The Basel ProDex Study targets improvement of hyperactive and mixed delirium therapy in critically ill patients. We will focus on reducing the duration and severity of delirium by implementing dexmedetomidine into the treatment plan. Dexmedetomidine compared with other sedatives shows fewer side effects representing a better risk profile for delirium treatment in general. This could further contribute to higher patient safety. The aim of the BaProDex Trial is to assess the superiority of dexmedetomidine to propofol for treatment of hyperactive and mixed delirium in the ICU. We hypothesise that dexmedetomidine, compared with propofol administered at night, shortens both the duration and severity of delirium. Methods/design: The Basel ProDex Study is an investigator-initiated, one-institutional, two-centre randomised controlled clinical trial for the treatment of delirium with dexmedetomidine versus propofol in 316 critically ill patients suffering from hyperactive and mixed delirium. The primary outcome measure is delirium duration in hours. Secondary outcomes include delirium-free days at day 28, death at day 28, delirium severity, amount of ventilator days, amount of rescue sedation with haloperidol, length of ICU and hospital stay, and pharmaceutical economic analysis of the treatments. Sample size was estimated to be able to show the superiority of dexmedetomidine compared with propofol regarding the duration of delirium in hours. The trial will be externally monitored according to good clinical practice (GCP) requirements. There are no interim analyses planned for this trial. Ethics and dissemination: This study will be conducted in compliance with the protocol, the current version of the Declaration of Helsinki, the International Conference on Harmonization- Good Clinical Practice (ICH-GCP) or Europäische Norm International Organization for Standardization (ISO EN 14155; as far as applicable) as well as all national legal and regulatory requirements. Only the study team will have access to trial specific data. Anonymisation will be achieved by a unique patient identification code. Trial data will be archived for a minimum of 10 years after study termination. We plan to publish the data in a major peer-reviewed clinical journal. Trials registration: ClinicalTrials.gov Identifier: NCT02807467 Protocol version: Clinical Study Protocol Version 2, 16.08.2016